What determines the optimal pharmacological treatment of atrial fibrillation? Insights from in silico trials in 800 virtual atria - Dasí, Albert; Pope, Michael T.B.; Wijesurendra, Rohan S.; Betts, Tim R.; Sachetto, Rafael; Bueno‐Orovio, Alfonso; Rodriguez, Blanca (The Journal of physiology, 2023)
The best pharmacological treatment for each atrial fibrillation (AF) patient is unclear. We aim to exploit AF simulations in 800 virtual atria to identify key patient characteristics that guide the optimal selection of anti-arrhythmic drugs. The virtual cohort considered variability in electrophysiology and low voltage areas (LVA) and was developed and validated against experimental and clinical data from ionic currents to ECG. AF sustained in 494 (62%) atria, with large inward rectifier K current (I ) and Na /K pump (I ) densities (I 0.11 ± 0.03 vs. 0.07 ± 0.03 S mF ; I 0.68 ± 0.15 vs. 0.38 ± 26 S mF ; sustained vs. un-sustained AF). In severely remodelled left atrium, with LVA extensions of more than 40% in the posterior wall, higher I (median density 0.12 ± 0.02 S mF ) was required for AF maintenance, and rotors localized in healthy right atrium. For lower LVA extensions, rotors could also anchor to LVA, in atria presenting short refractoriness (median L-type Ca current, I , density 0.08 ± 0.03 S mF ). This atrial refractoriness, modulated by I and fast Na current (I ), determined pharmacological treatment success for both small and large LVA. Vernakalant was effective in atria presenting long refractoriness (median I density 0.13 ± 0.05 S mF ). For short refractoriness, atria with high I (median density 8.92 ± 2.59 S mF ) responded more favourably to amiodarone than flecainide, and the opposite was found in atria with low I (median density 5.33 ± 1.41 S mF ). In silico drug trials in 800 human atria identify inward currents as critical for optimal stratification of AF patient to pharmacological treatment and, together with the left atrial LVA extension, for accurately phenotyping AF dynamics. KEY POINTS: Atrial fibrillation (AF) maintenance is facilitated by small L-type Ca current (I ) and large inward rectifier K current (I ) and Na /K pump. In severely remodelled left atrium, with low voltage areas (LVA) covering more than 40% of the posterior wall, sustained AF requires higher I and rotors localize in healthy right atrium. For lower LVA extensions, rotors can also anchor to LVA, if the atria present short refractoriness (low I ) Vernakalant is effective in atria presenting long refractoriness (high I ). For short refractoriness, atria with fast Na current (I ) up-regulation respond more favourably to amiodarone than flecainide, and the opposite is found in atria with low I . The inward currents (I and I ) are critical for optimal stratification of AF patient to pharmacological treatment and, together with the left atrial LVA extension, for accurately phenotyping AF dynamics.